A novel COL2A1 mutation in a Chinese family with predominantly ocular Stickler syndrome - Lin, Yanyu; Liu, Xin; Lin, Shuxian; Lin, Jiansheng (Frontiers in Genetics, 2025)
PurposeThe ocular-only variant of Stickler syndrome type I (OSTL1) is an autosomal dominant connective tissue disorder characterized by ocular abnormalities with minimal or absence of systemic involvement. This study aimed to investigate the clinical features and molecular etiology of predominantly ocular Stickler syndrome in a multigenerational pedigree.MethodsComprehensive ophthalmic, audiological, and physical examinations were conducted on family members with predominantly ocular Stickler syndrome. Whole exome sequencing (WES) was conducted on the proband, and Sanger sequencing was used to confirm co-segregation of the identified mutation within the family.ResultsTwo affected individuals were identified, both presenting with myopia, megalophthalmos, retinal tears and detachment, vitreous opacification, chorioretinal scars, and early-onset cataracts. The proband’s mother had complete vision loss in her right eye. In terms of extraocular findings, the proband presented with scoliosis, and the proband’s mother had mild hearing loss in both ears. A novel likely pathogenic (LP) frameshift mutation c.3534dupT (p.Gly1179Trpfs*74) in exon 50 of the COL2A1 was identified in both affected individuals and absent in unaffected family members. This mutation was not found in the ESP, 1000 Genomes, or EXAC databases and is predicted to cause protein truncation.ConclusionThis study reports, for the first time, the clinical manifestations associated with a novel COL2A1 exon 50 mutation in a family with predominantly ocular Stickler syndrome. Our findings expand the known mutational spectrum of COL2A1 and further illustrate the phenotypic variability of an ocular variant of Stickler syndrome type I with minimal systemic manifestations. These results highlight the importance of early screening in individuals at risk to enable timely diagnosis and management.